Temporal transcriptome analysis reveals several key pathways involve in cadmium stress response in Nicotiana tabacum L. - Li, Chenyang; Hong, Yi; Sun, Jinhao; Wang, Guoping; Zhou, Huina; Xu, Liangtao; Wang, Long; Xu, Guoyun (Frontiers in Plant Science, 2023)
Tobacco has a strong cadmium (Cd) enrichment capacity, meaning that it can absorb large quantities from its environment, but too much Cd will cause damage to the plant. While previous studies have sought to understand how tobacco accumulates Cd, it is not yet clear how the plant can dynamically respond to Cd stress. Here, we performed a temporal transcriptome analysis of tobacco roots under Cd treatment from 0 to 48 h. The number of differentially expressed genes (DEGs) was found to change significantly at 3 h of Cd treatment, which we used to define the early and middle stages of the Cd stress response. The gene ontology (GO) term of our DEGs analysis indicates that genes related to photosynthesis and fatty acid synthesis are enriched during the early phases of the stress response, and in the middle phase biological process related to metal ion transport, DNA damage repair, and metabolism are enriched. It was also found that plants use precursor mRNA (pre-mRNA) processes to first resist Cd stress, and with the increasing of Cd treatment time, some different alternative splicing genes gradually cause changes in gene expression. This study allows us to better understand how plants dynamically respond to cadmium stress at the transcriptional and post-transcriptional levels and provides a reference for the selection of Cd tolerant tobacco varieties in the future.